2022
DOI: 10.1002/celc.202200156
|View full text |Cite
|
Sign up to set email alerts
|

Sb‐ and O‐Cosubstituted Li10SnP2S12 with High Electrochemical and Air Stability for All‐Solid‐State Lithium Batteries

Abstract: The development of solid‐state electrolytes with high ionic conductivity, broad electrochemical stability, and high air stability is the key to realizing the practical application of all‐solid‐state batteries. Herein, Sb‐ and O‐cosubstituted Li10SnP2S12 sulfide electrolytes are prepared for the first time. An appropriate amount of Sb and O substitution provides the optimized Li10SnP1.84Sb0.16S11.6O0.4 electrolyte with the highest ionic conductivity of 2.58 mS ⋅ cm−1 at RT. Furthermore, the cyclic voltammetry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The reported Raman signals for the (SbS 4 ) 3− symmetric vibrations range in between 360 cm −1 to 368 cm −1 , 12,41,42 and for the asymmetric stretching mode at 389 cm −1 and 410 cm −1 or 421 cm −1 . 24,41,42 Thus, the occurring peak should be the asymmetric stretch of the (SbS 4 ) 3− unit suggesting that the symmetric stretch of the (SbS 4 ) 3− unit is hidden beneath the symmetric stretch of the (GeS 4 ) 4− unit. To summarize, the Raman indicates that the bond strength of the (PS 4 ) 3− unit is not influenced due to the similarity of the observed wavenumbers for every composition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported Raman signals for the (SbS 4 ) 3− symmetric vibrations range in between 360 cm −1 to 368 cm −1 , 12,41,42 and for the asymmetric stretching mode at 389 cm −1 and 410 cm −1 or 421 cm −1 . 24,41,42 Thus, the occurring peak should be the asymmetric stretch of the (SbS 4 ) 3− unit suggesting that the symmetric stretch of the (SbS 4 ) 3− unit is hidden beneath the symmetric stretch of the (GeS 4 ) 4− unit. To summarize, the Raman indicates that the bond strength of the (PS 4 ) 3− unit is not influenced due to the similarity of the observed wavenumbers for every composition.…”
Section: Resultsmentioning
confidence: 99%
“…19 Gao et al found an increase in unit cell volume by co-substituting Li 10 SnP 2 S 12 with Sb and O, achieving the highest conductivity of 2.58 mS cm −1 for Li 10 SnP 1.84 Sb 0.16 S 11.6 O 0.4 . 24 The introduction of oxygen led to a blue shift of the (SnS 4 ) 4− and (PS 4 ) 3− vibrational energies, and an additional signal at 421 cm −1 in the Raman spectrum, which is attributed to the (SbS 4 ) 3− unit. 24 Wang et al found that the solubility limit of antimony in the substitution series Li 10 SnP 2− x Sb x S 12 is x (Sb) = 0.2, and that the antimony substitution does not affect the vibrations of (SnS 4 ) 4− and (PS 4 ) 3− in the Raman spectra.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Liu et al prepared a series of Li 10 Sn 0.95 P 2 S 11.9−x O x (0 ≤ x ≤ 1) by the solid-phase sintering method and Li 10 Sn 0.95 P 2 S 11.4 O 0.5 shows high conductivity of 3.96 × 10 −3 S·cm −1 with a negligible decrease after exposed in the air [ 172 ]. Gao et al were first to prepare Sb 5+ and O 2− substituted Li 10 SnP 2 S 12 with high air stability due to the soft acid Sb 5+ and hard base O 2− dual substitution [ 173 ]. The Li 10 SnP 1.84 Sb 0.16 S 11.6 O 0.4 electrolyte displays a broader electrochemical window of 1.4–5.0 V vs. Li + /Li and ionic conductivity of 2.58 × 10 −3 S·cm −1 .…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…[17] Figure 5 shows other examples from the literature. [55][56][57][58][59][60][61][62][63][64][65] Figure 5a shows the isokinetic prefactor 𝜎 00 as a function of the reciprocal of isokinetic temperature T iso for some perovskitetype proton conductors. Neutron scattering experiments have also confirmed that for perovskite proton conductors, the proton jump time follows a polaron model.…”
Section: Relationship Between Isokinetic Temperature and Isokinetic P...mentioning
confidence: 99%